Strengthening Halal Tourism Based on Prophetic Islamic Law through The Historical Social Inference of the Sasak, Samawa and Mbojo - Nurjannah S; Rina Rohayu H; Khudzaifah Dimyati; Absori Absori (IJECA (International Journal of Education and Curriculum Application), 2018)
The legal paradigm of halal tourism which is being built by the government West Nusa Tenggara Province is based on oriental characters, civilization, and culture with the main scheme to attract the world Muslim tourists. The development of legal paradigm of character-and-civilized-based tourism is important in order to establish local identity of a particular area, which is now declining. This paper aimed to discus legal concept of halal tourism based on Islamic prophetic through social historical inference of Sasak, Samawa, and Mbojo ethnic groups. This research used legal analysis method of sociological jurisprudence and prophetic legal method with integrated-interconnected approach through the procedure of social historical interference. The finding revealed there is a convergence of Islamic prophetic values and social historical values of Sasak, Samawa, and Mbojo reflected in the patterns of halal food, social relation, clothes, economy, and the like. Common philosophy of Sasak, Samawa, and Mbojo, that is “adat bersendi syara’, syara’ bersendi kitabullah” (tradition is based upon sharia, sharia is based upon the Book of Allah) supports the Islamic identity that has provided a foundation for the issuance of halal regulation and the accommodation of character and civilized based local identities through local friendly entities.